SUBSTANTIATION OF GRAPHICAL METHOD OF TOOTH SPACE SHAPING FOR THE WHEEL WITH ASYMMETRIC PROFILES - P. A. KARGIN (Advanced Engineering Research, 2010)
Substantiation of graphical method of plotting the tooth root fillet curves of involute wheel teeth with large asymmetry of profiles suitable for construction of self-braking tooth gear drives of load-lifting machines is described. Inversion method is applied to obtain relative locations of the second mating gear teeth. The described fillet curve with due clearance covers the found complex of the second gear teeth positions.